2010
DOI: 10.1007/s10534-010-9297-1
|View full text |Cite
|
Sign up to set email alerts
|

A critical review of the roles of host lactoferrin in immunity

Abstract: Lactoferrin (Lf) is an essential element of innate immunity, which refers to antigen-nonspecific defense mechanisms that a host uses immediately or within hours after exposure to an antigen. Following infection, Lf is released from neutrophils (PMNs) in blood and inflamed tissues and, such as other soluble pattern-recognition receptors of the innate immunity, Lf recognizes unique microbial molecules called pathogen-associated molecular patterns (PAMPs): LPS from the gram-negative cell wall and bacterial unmeth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
94
1
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 148 publications
(96 citation statements)
references
References 85 publications
0
94
1
1
Order By: Relevance
“…[13][14][15] LF has bacteriostatic and bactericidal activities and is involved in host immune defense. 13,16,17 There are some reports that LF can inhibit the adhesion of oral bacteria and Candida albicans on hydroxyapatite, 18,19 dental polymers, 20 and glass disks. 21 However, there are no reports about the effect of a LF coating on dental abutment materials.…”
Section: 2mentioning
confidence: 99%
“…[13][14][15] LF has bacteriostatic and bactericidal activities and is involved in host immune defense. 13,16,17 There are some reports that LF can inhibit the adhesion of oral bacteria and Candida albicans on hydroxyapatite, 18,19 dental polymers, 20 and glass disks. 21 However, there are no reports about the effect of a LF coating on dental abutment materials.…”
Section: 2mentioning
confidence: 99%
“…Multiple biological functions have been described for LF, including iron homeostasis, antiinflammatory activity, immunomodulation, cancer protection, and antimicrobial activity. [13][14][15] Although the cellular and molecular mechanisms accounting for the immunemodulatory effects of LF are far from being fully elucidated, it is now clear that the capacity of LF to influence cytokine production, either negatively or positively, relies, at least in part, on its ability to bind and sequester both lipopolysaccharide and its receptor CD14, as well as CpG DNA, thus preventing the downstream activation of pro-inflammatory pathways. [16][17][18] Through the linkage analysis of 18 pedigrees from the Hunan province of South China, we previously revealed that potential susceptibility loci related to NPC are located on chromosome 3p21.…”
mentioning
confidence: 99%
“…Most iron is sequestered within cells, and serum iron is kept at an extremely low concentration (ϳ10 Ϫ24 M) by the iron transport protein transferrin (2). A related protein, lactoferrin, is present in exocrine solutions such as tears and milk and is also released from neutrophils at sites of infection (3). Iron uptake and homeostasis are even tuned toward anemia in chronic infection by the hormone hepcidin (4).…”
mentioning
confidence: 99%